Epididymis metastasis in adenocarcinoma lung: A rare entity - Thakur, Shabnum; Gupta, Manish; Fotedar, Vikas (Indian Journal of Case Reports, 2020)
Testicular neoplasms constitute for only 1% of all malignancies. Testicular metastasis are seldom seen. A testicular metastasis classically presents as a complication of progressive disease or as a primary sign of malignancy. Excluding lymphoma and leukemia, prostate cancer is the most frequent primary site that metastasizes to the testes. Testicular metastasis resulting from adenocarcinoma of the lung have rarely been reported in the literature. Here, we are reporting a case of adenocarcinoma lung with metastasis to the epididymis. Histopathological examination confirmed that this was an epididymis metastasis of adenocarcinoma having origin from the lung.